Comment - Louis XIV’s terminal illness clinical chronology favors necrotizing soft-tissue infection - Alexis Demas (BMC Nephrology, 2026)
Abstract Louis XIV’s rapidly progressive terminal illness may be better explained by necrotizing soft-tissue infection than primary calciphylaxis. Severe distal pain, ascending gangrene, and fatal sepsis within three weeks suggest fulminant infection, plausibly arising from a diabetic foot lesion. Clinical chronology should remain central when evaluating competing retrospective clinicopathological hypotheses.